1972
DOI: 10.1007/bf02582528
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of the reaction between chlorine and oleic acid in carbon tetrachloride solution

Abstract: Kinetic data have been obtained for the reaction between chlorine and oleic acid in carbon tetrachloride solution by measuring the chlorine depletion and hydrogen chloride production as a function of residence time in a rod-like flow system. The data are well correlated by a kinetic model incorporating parallel, second-order addition and substitution reactions. Measured reaction rates are an order of magnitude less than those reported in a previous investigation which neglected substitution reactions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

1979
1979
2011
2011

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…20 Clegg and Winter studied kinetics of the reaction between chlorine and oleic acid in carbon tetrachloride solution. 21 The process involves gas absorption with chemical reaction, which involves large heat generation. The reaction between chlorine and oleic acid is highly exothermic with negligible evaporation effect for the oleic acid.…”
Section: Case Study-absorption Of Chlorine In Oleic Acid Using Lamina...mentioning
confidence: 99%
See 3 more Smart Citations
“…20 Clegg and Winter studied kinetics of the reaction between chlorine and oleic acid in carbon tetrachloride solution. 21 The process involves gas absorption with chemical reaction, which involves large heat generation. The reaction between chlorine and oleic acid is highly exothermic with negligible evaporation effect for the oleic acid.…”
Section: Case Study-absorption Of Chlorine In Oleic Acid Using Lamina...mentioning
confidence: 99%
“…According to the work of Clegg and Winter, it was expected that interfacial turbulence would not be present in this system because of the high viscosity of the oleic acid. 21 3.3. Modeling.…”
Section: Case Study-absorption Of Chlorine In Oleic Acid Using Lamina...mentioning
confidence: 99%
See 2 more Smart Citations
“…They found that in the presence of light 9,10-dichlorostearic acid formation was accompanied by dimer and trimer formation. Clegg and Winter (1972) chlorinated oleic acid dissolved in carbon tetrachloride in the presence of light and in the temperature range 25 to 44 °C. Their results were well correlated by a kinetic model incorporating second-order addition and substitution reactions.…”
mentioning
confidence: 99%